Mandatory and discretional non-financial disclosure after the European directive 2014/95/EU : an empirical analysis of Italian listed companies' behavior - De Luca, Francesco (Emerald Publishing Limited, 2020)
The aim of the EU Directive 2014/95/EU, requiring the mandatory disclosure of non-financial information (NFI) by large undertakings and groups, is to rebuild trust with stakeholders. This book aims to summarize the relevant literature about company information with particular reference to the voluntary vis a vis mandatory NFI.
Includes index.
Keywords: Business ethics.; Business & Economics -- Business Ethics.; Business ethics & social responsibility.; elektronické knihy; electronic books